Integrating the Audio-oral Method and Wordwall Gamification in Teaching Arabic Speaking and Grammar: A Case Study at The New College, Chennai - Dr K M A AHAMED ZUBAIR (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
This study investigates the integration of two pedagogical approaches-the Audio-Oral Method and Wordwall game-based learning-in teaching Arabic speaking skills and grammar at the Department of Arabic, The New College, Chennai. Employing a qualitative case study design, data were collected through classroom observations, interviews with instructors and students, and analysis of instructional materials. The study involved 30 undergraduate students divided into two proficiency-based groups. Findings reveal that the Audio-Oral Method effectively enhances pronunciation and dialogue practice through repetition and translation, while Wordwall serves as an engaging formative assessment tool that increases student motivation, vocabulary retention, and collaborative learning. However, challenges include the lack of an immersive Arabic language environment, local language interference, monotonous teaching practices, and unequal student participation in gamified activities. The study concludes that blended use of these methods can significantly improve Arabic language acquisition if supported by structured planning, diversified teaching strategies, and equitable classroom engagement techniques.